Assortment of varieties of malting barley in the Czech Republic in the year 2000 - Psota, V.; Kosař, K.; Jurečka, D. (BrewingScience, 2001)
In this paper, results of micromalting and malt and wort analyses of 16 barley cultivars registered in the Czech Republic for the year 2000 are presented. This study is a continuation of the article published by Psota and Kosar (1996) and presents a survey of changes in the assortment of malting barley cultivars in the Czech Republic within the last four years.